Register of Rice Farmers in Petemon Area of Pagutan Timur Village Mataram District: A Sociolinguistic Study - Ida Royani; I Nyoman Sudika; Wika Wahyuni (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The rice farming community in Petemon uses a distinctive vocabulary that reflects a local register not found outside the community. Agricultural modernization, land conversion, and generational shifts have threatened the existence of many of these local terms. This study aims to describe the forms and meanings of the rice farmers register in Petemon, East Pagutan Village, Mataram District. Employing a descriptive qualitative approach, data were collected through introspection, observation, and interviews. The data were analyzed using intralingual and extralingual comparison methods with comparative techniques. The findings reveal two types of register restricted and open used across six stages of rice farming activities: pre-planting, land preparation, planting, maintenance, harvesting, and post-harvesting. The linguistic units consist of words and phrases, predominantly verbs and nouns.